Respuestas
Respuesta dada por:
1
Para derivar esto sabes que
Donde, u es la función y u' su derivada
![f(x)= e^{4-x^2} <br />f'(x)= e^{4-x^2} * (4-x^2)'
f(x)= e^{4-x^2} <br />f'(x)= e^{4-x^2} * (4-x^2)'](https://tex.z-dn.net/?f=f%28x%29%3D++e%5E%7B4-x%5E2%7D+%3Cbr+%2F%3Ef%27%28x%29%3D+e%5E%7B4-x%5E2%7D+%2A+%284-x%5E2%29%27%0A)
![f'(x)= e^{4-x^2} * (-2x^(2-1))
f'(x)= e^{4-x^2} * (-2x^(2-1))](https://tex.z-dn.net/?f=f%27%28x%29%3D+e%5E%7B4-x%5E2%7D+%2A+%28-2x%5E%282-1%29%29%0A)
![f'(x)= e^{4-x^2} * (-2x^1)' f'(x)= e^{4-x^2} * (-2x^1)'](https://tex.z-dn.net/?f=f%27%28x%29%3D+e%5E%7B4-x%5E2%7D+%2A+%28-2x%5E1%29%27)
![f'(x) = e^{4-x^2} (-2x) f'(x) = e^{4-x^2} (-2x)](https://tex.z-dn.net/?f=f%27%28x%29+%3D+e%5E%7B4-x%5E2%7D+%28-2x%29)
Respuesta dada por:
1
derivada externa por interna:
![( {e}^{4 - {x}^{2} }) \\ {e}^{4 - {x}^{2} } ( - 2x) ( {e}^{4 - {x}^{2} }) \\ {e}^{4 - {x}^{2} } ( - 2x)](https://tex.z-dn.net/?f=%28+%7Be%7D%5E%7B4+-++%7Bx%7D%5E%7B2%7D+%7D%29++%5C%5C+%7Be%7D%5E%7B4+-++%7Bx%7D%5E%7B2%7D+%7D+%28+-+2x%29)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años